The effect of kinesiology taping on gait variability in healthy dogs - Liu, Ching-Ming; Lin, Syu-Lun; Liu, Hsiao-Man; Huntingford, Janice L. (Frontiers in Veterinary Science, 2025)
IntroductionKinesiology taping is commonly utilized in sports and rehabilitation for both humans and horses. Evaluating its effectiveness includes both subjective and objective kinesiology assessments. However, there is limited research on the use of kinesiology taping in dogs. This study examines the effects of kinesiology taping on gait variability in healthy dogs.Materials and methodsA total of eight client-owned dogs varying in age, breed, and body weight were recruited for the study. Three taping methods were applied to the biceps femoris muscle. Mobility, as well as static and dynamic parameters, were assessed using a scale, a stance analyzer, and a pressure-sensitive walkway for data collection and statistical evaluation.ResultsKinesiology taping on clinically healthy dogs had minimal impact on mobility and stance, and only a partial intrinsic effect on gait. Only 3 of 29 kinetic and temporospatial parameters showed a statistically significant difference (p < 0.05) between taping types. Over days with different taping methods, the number of significantly affected kinetic and temporospatial variable items ranged between 2 and 7 out of 29, with inconsistent distribution. The effect of taping on gait also varied depending on whether hair was present or clipped.DiscussionThese findings suggest that kinesiology taping has minimal and inconsistent effects on gait variables in healthy dogs, with limited variation across taping methods and a moderate influence due to the presence of hair. This study provides preliminary data on intrinsic neuromuscular modulation in response to skin stimulation, enhancing our understanding of canine gait biomechanics. The insights gained may help guide future research into dynamic stability, compensatory strategies, and neurosensory responses during healthy movement in healthy dogs.